(untitled) - Muench, Steve (Cambridge, Mass., 2000)
Building Oracle XML Applications introduces XML, gives an overview of Oracle XML technologies, and shows what they do and how they fit together. There is a focus on JDeveloper, Oracle's Java and XML development tool, which can be installed from the CD-ROM, and there are plenty of hands-on examples of how to use it. Then there are chapters on processing XML with PL/SQL or Java, transforming XML with XSLT, publishing data with XSQL pages, generating datagrams (XML documents used for exchanging data), and techniques for storing and loading XML data. The final section concentrates on Oracle XML applications, and topics include an XSQL publishing framework, Java extension functions, and using XSQL and XSLT to build personalized portals and discussion forums.
Keywords: Oracle (tệp máy tính),Oracle (Computer file)